2007
DOI: 10.1016/j.bcp.2007.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity of MATE1 and MATE2-K, human multidrug and toxin extrusions/H+-organic cation antiporters

Abstract: The substrate specificities of human (h) multidrug and toxin extrusion (MATE) 1 and hMATE2-K were examined to find functional differences between these two transporters by the transfection of the cDNA of hMATE1 and hMATE2-K into HEK293 cells. Western blotting revealed specific signals for hMATE1 and hMATE2-K consistent with a size of 50 and 40kDa, respectively, in the transfectants as well as human renal brush-border membranes under reducing conditions. In the presence of oppositely directed H(+)-gradient, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
290
1
5

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 362 publications
(312 citation statements)
references
References 23 publications
13
290
1
5
Order By: Relevance
“…[15][16][17] On the other hand, Shikata et al 25 reported that OCT1 and OCT2 polymorphisms contribute little to the clinical efficacy of metformin in Japanese. Previously, we demonstrated that metformin is a good substrate not only for OCT2 but also for MATE1 and MATE2-K. 19,26 Therefore, the SNPs of MATE1 and MATE2-K genes identified in this study may be involved in the interindividual difference in the renal clearance of metformin in Japanese. However, as the allelic frequencies of MATE1 and MATE2-K SNPs are not very high, these SNPs cannot fully account for the large interindividual variation in the renal clearance of metformin.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…[15][16][17] On the other hand, Shikata et al 25 reported that OCT1 and OCT2 polymorphisms contribute little to the clinical efficacy of metformin in Japanese. Previously, we demonstrated that metformin is a good substrate not only for OCT2 but also for MATE1 and MATE2-K. 19,26 Therefore, the SNPs of MATE1 and MATE2-K genes identified in this study may be involved in the interindividual difference in the renal clearance of metformin in Japanese. However, as the allelic frequencies of MATE1 and MATE2-K SNPs are not very high, these SNPs cannot fully account for the large interindividual variation in the renal clearance of metformin.…”
Section: Discussionmentioning
confidence: 55%
“…[15][16][17] Metformin showed large interindividual variation in renal clearance, and a potential genetic contribution by the renal transporter was speculated. 18 Because metformin is also a superior substrate for MATE1 and MATE2-K, 10,19 polymorphisms of MATE1 and MATE2-K genes may be involved in the interindividual difference in the renal clearance. We have recently identified a single nucleotide polymorphism (SNP) in the promoter region of MATE1 (À32G4A), which causes a decrease in Sp1 binding and promoter activity of approximately 50%.…”
Section: Introductionmentioning
confidence: 99%
“…Metformin is a comparatively low-affinity substrate for hOCT1, hOCT2, hMATE1, and hMATE2-K, with K t values of 1.47, 0.99, 0.78, and 1.98 mM, respectively (Koepsell et al, 2007;Tanihara et al, 2007). As determined here, NBuPy-Cl blocks both OCTs and MATEs with IC 50 values in the low micromolar range.…”
Section: Inhibitory Effects Of Ionic Liquids On Octs and Matesmentioning
confidence: 49%
“…This may be one of the reasons for its toxicity reducing effect. In spite of above well known transporters there are some transporters such as Mate1-2, RLIP76, and aquaporin, may play a role in meridian guide effect (Tanihara 2007, Ohta et al, 2009Singhal, 2009). For example, carbamazepine is an active drug for epilepsy, and it has drug-resistant phenomenon.…”
Section: Meridian Guide Drug and Transportersmentioning
confidence: 99%